Passive energy dissipation-based retrofit strategies for R/C frame water towers. (1st January 2016) - Sorace, Stefano; Terenzi, Gloria; Mori, Claudia
Highlights: Pre-normative R/C water towers are among the most seismically vulnerable structures in urban areas. An emblematic case study designed by Pier Luigi Nervi in the early 1930s is examined. Collapse conditions are found for the structure at the maximum considered earthquake (MCE) level. Two dissipative bracing retrofit solutions, incorporating viscous or steel dampers, are proposed. The two protective systems allow attaining an elastic response up to the MCE. Abstract: Pre-normative elevated liquid storage tanks with reinforced concrete (R/C) frame staging are among the most seismically vulnerable structures in urban areas, due to their unfavourable earthquake-resistant configuration. A representative case study, i.e. a R/C water tower designed by the world-famous Italian engineer Pier Luigi Nervi and built in the early 1930s, is examined herein. The assessment of the structure was developed with a detailed finite element model, which includes a multi spring-mass assembly to reproduce the fluid–tank dynamic interaction. The time-history evaluation analysis, initially carried out by assuming an elastic behavior of the staging members, showed general unsafe response conditions of beams and columns under seismic action scaled at the maximum considered earthquake (MCE) level. These results were confirmed at a second step of the analysis, where the plastic behavior of beams and columns was investigated after incorporating lumped plastic hinges at their end sections, which resulted in the collapse of the model. Based on these data, two passive energy dissipation-based retrofit measures were proposed, for which dissipative bracing systems incorporating either pressurized fluid viscous spring-dampers or added damping and stiffness steel yielding devices, respectively, were installed. The two systems were designed with a mutual energy-based criterion and for the same target performance objectives, that is, reaching elastic response up to the MCE. The benefits induced by the two protective systems to the seismic response of the tank structure are discussed, and the geometrical dimensions and relevant architectural impact are compared with the ones of a conventional non-dissipative bracing retrofit solution developed for the same performance.